2000
DOI: 10.1128/iai.68.9.5218-5224.2000
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Adhesin, Ace, Mediates Attachment to Extracellular Matrix Proteins Collagen Type IV and Laminin as well as Collagen Type I

Abstract: Adhesin-mediated binding to extracellular matrix (ECM) proteins is thought to be a crucial step in the pathogenic process of many bacterial infections. We have previously reported conditional adherence of most Enterococcus faecalis isolates, after growth at 46°C, to ECM proteins collagen types I and IV and laminin; identified an E. faecalis-specific gene, ace, whose encoded protein has characteristics of a bacterial adhesin; and implicated Ace in binding to collagen type I. In this study, we constructed an ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
217
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 210 publications
(238 citation statements)
references
References 40 publications
15
217
1
5
Order By: Relevance
“…In addition to the six novel putative enterococcal MSCRAMM proteins, ACE (EF1099), which can act as a collagen/laminin-binding adhesin (Nallapareddy et al, 2000b;Rich et al, 1999), was also identified in our search and characterized for comparison. We have recently been able to crystallize the A-region of ACE (Ponnuraj et al, 2002).…”
Section: Expression Purification and Characterization Of Putative A-mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the six novel putative enterococcal MSCRAMM proteins, ACE (EF1099), which can act as a collagen/laminin-binding adhesin (Nallapareddy et al, 2000b;Rich et al, 1999), was also identified in our search and characterized for comparison. We have recently been able to crystallize the A-region of ACE (Ponnuraj et al, 2002).…”
Section: Expression Purification and Characterization Of Putative A-mentioning
confidence: 99%
“…ACE, a collagen-binding adhesin of the MSCRAMM (microbial surface component recognizing adhesive matrix molecules) family is an exception. This protein was previously identified in our laboratories based on its sequence similarity to the staphylococcal MSCRAMM CNA (Nallapareddy et al, 2000b;Rich et al, 1999). Both proteins bind to multiple sites in collagen but with different kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…E. faecalis strains recovered from patients with endocarditis have a greater capacity to adhere to Girardi heart cells than to urinary tract epithelial cells in vitro (6), which suggests that adherence to vascular endothelium may be important. MSCRAMMs mediate binding of bacteria to extracellular matrix proteins and function as adhesins to damaged heart tissue (17,18,27). Ace is a specific collagen-binding adhesin of the MSCRAMM family, has been identified in E. faecalis endocarditis isolates (17), and mediates attachment of E. faecalis to collagen types I and IV and laminin (18).…”
mentioning
confidence: 99%
“…These included the gelatinase gene (22,26,28,30); recently described pilus-encoding genes (16); genes encoding putative MSCRAMMs (microbial surface components recognizing adhesive matrix molecules) with predicted immunoglobulin (Ig)-like folds (17,18,27; J. Sillanpää, S. R. Nallapareddy, and B. E. Murray, unpublished data); genes, including esp (33), in a predicted pathogenicity island (PAI) (15); and an acquired gene that contributes to biofilm formation (32) ( Table 1). The strain was examined for phenotypic production of gelatinase (22), hemolytic activity on Bacto Tryptic Soy Agar (Becton Dickinson and Company, Sparks, MD) plus 5% human blood agar plates, and biofilm formation (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation